2013
DOI: 10.3892/mmr.2013.1553
|View full text |Cite
|
Sign up to set email alerts
|

1,3-β-Glucan affects the balance of Th1/Th2 cytokines by promoting secretion of anti-inflammatory cytokines in vitro

Abstract: Abstract. 1,3-β-glucan is considered a fungal biomarker and exposure to this agent induces lung inflammation. Previous studies have shown that 1,3-β-glucan affects Th1 and Th2 immune responses. Interleukin (IL)-10 and transforming growth factor (TGF)-β, as typical anti-inflammatory cytokines, suppress the Th1 immune response. To investigate the effects of 1,3-β-glucan on the secretion of cytokines in co-cultured mouse macrophages and lymphocytes in vitro, mice were exposed to 1,3-β-glucan or phosphate-buffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Recent reports show that curdlan can inhibit T H 2-cell responses, promoting breast cancer progression [43]; it was also reported to suppress IL-5, IL-13 and surprisingly IL-1β www.eji-journal.eu from lymph nodes during epicutaneous sensitization [44]. Conversely, β-glucan treatment can increase T H 2-cell cytokine secretion from cocultured macrophages and lymphocytes [45] and stimulate production of both proallergic (IL-33, CCL17, CCL22) and inflammatory (IL-1β and CXCL1) mediators during lung exposure to Aspergillus fumigatus, in a dectin-1-dependent manner [46]. Furthermore, in addition to TSLP we have observed that β-glucanstimulated mDCs generate large quantities of CCL22 (data not shown) emphasizing that mDCs can secrete pro-T H 2-cell factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports show that curdlan can inhibit T H 2-cell responses, promoting breast cancer progression [43]; it was also reported to suppress IL-5, IL-13 and surprisingly IL-1β www.eji-journal.eu from lymph nodes during epicutaneous sensitization [44]. Conversely, β-glucan treatment can increase T H 2-cell cytokine secretion from cocultured macrophages and lymphocytes [45] and stimulate production of both proallergic (IL-33, CCL17, CCL22) and inflammatory (IL-1β and CXCL1) mediators during lung exposure to Aspergillus fumigatus, in a dectin-1-dependent manner [46]. Furthermore, in addition to TSLP we have observed that β-glucanstimulated mDCs generate large quantities of CCL22 (data not shown) emphasizing that mDCs can secrete pro-T H 2-cell factors.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Some in vitro studies have also supported the beneficial effects of β-glucan on the immune system. [14,15] Studies on humans have shown that the administration of soluble fiber or intravenous β-glucan in trauma patients and in patients with severely acute pancreatitis reduced the infection, length of ICU stay, and septic morbidity. [16][17][18] Unfortunately, most studies have been done in vitro or on animals.…”
mentioning
confidence: 99%
“…Glucans are well known to stimulate production and secretion of various cytokines, with a wide range from IL-1, IL-2, and IL-6 to TNFα, and IFNγ [26,27]. In fact, there is only one known glucan without any significant stimulation of cytokine production [28].…”
Section: Discussionmentioning
confidence: 99%